PENGARUH KOMBINASI TERAPI COUNTERPRESSURE DENGAN BIRTH BALL TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF DI KLINIK CITRA MARENDAL - Tane, Reisy; Silalahi, Rini Debora; Angriawan, Angriawan (Jurnal Penelitian Keperawatan Medik, 2024)
Background: Childbirth is the birth of the baby, placenta, and amniotic membranes from the uterus to the outside world. During labor, it can cause trauma to the mother because of the pain experienced. Some mothers are even traumatized to get pregnant and give birth again because they are afraid they will experience the same pain, especially for mothers who have given birth for the first time. Nonpharmacological therapy to reduce pain can be done counterpressure with a combination of birth balls. Objective: To determine the effect of a combination of counter pressure therapy with a birth ball on reducing active phase I labor pain. Method: This research used a quasi experiment with a two group only post test design. The population in this study were all mothers giving birth at the Citra Marendal clinic with a total sample of 36 people, each group consisting of 18 people. The instruments used were Numeric Rating Scale sheets and observations, with the Mann-Whitney Test hypothesis test. Conclusion: There is an effect of a combination of counter pressure therapy with a birth ball on reducing active phase I labor pain at the Citra Marendal Delitua Clinic with a p value = 0.001 <0.05. Suggestion: For the future, it is hoped that they can develop research by examining various complementary methods that can reduce labor pain such as: the effectiveness of music therapy, aroma therapy, back massage, gym ball/birth ball techniques, relaxation techniques, remembrance, guided imagery.